The A component (SmhA) of a tripartite pore-forming toxin from Serratia marcescens: expression, purification and crystallographic analysis - Churchill-Angus, Alicia M. (Acta Crystallogr F Struct Biol Commun, 2020)
Tripartite α-pore-forming toxins are constructed of three proteins (A, B and C) and are found in many bacterial pathogens. While structures of the B and C components from Gram-negative bacteria have been described, the structure of the A component of a Gram-negative α-pore-forming toxin has so far proved elusive. SmhA, the A component from the opportunistic human pathogen Serratia marcescens, has been cloned, overexpressed and purified. Crystals were grown of selenomethionine-derivatized protein and anomalous data were collected. Phases were calculated and an initial electron-density map was produced.